Diagnostic challenges of an unusually large schwannoma of the mandible: Report of a case - Manal Alsheddi; Mohammed Alkindi; Mohammed Badwelan; Noura Alotaibi; Sundar Ramalingam (Elsevier, 2018)
Schwannomas are slow-growing, benign neoplasms arising from the Schwann cells and are commonly reported as peripheral tumors in the head and neck region. Central intramandibular schwannomas are extremely rare lesions. We report a case of intramandibular schwannoma in a 70 year old male patient. Panoramic radiography revealed a large, multilocular radiolucent lesion with distinct borders involving the right mandibular body and ramus. A complete excision was achieved by removing the tumor followed by reconstruction of the mandible. The clinical, radiological, and histopathological features are discussed within the context of this case. Keywords: Schwannoma, Intramandibular schwannoma, Mandible